Teacher Evaluation of a Self-Directed Career Guidance Intervention for South African Secondary School Learners Amidst Severe COVID-19 Restrictions - van Schalkwyk, Izanette; Streicher, Chantel; Naidoo, Anthony V.; Rabie, Stephan; Jäckel-Visser, Michelle; van den Berg, Francois (Frontiers in Psychology, 2022)
The South African government’s COVID-19 pandemic risk mitigation strategies significantly limited social contact, which necessitated a novel approach to existing face-to-face career guidance practices. The Grade 9 Career Guidance Project, originally developed as a group-based career development intervention, required radical adaptation into a self-directed, manualized format to offer career guidance to Grade 9 learners from low-income communities amid a global pandemic. The adaptation and continuation of the project was deemed essential as secondary school learners in low-income communities have limited career guidance support. Furthermore, a close collaboration with the teachers at eight resource-constrained South African secondary schools was vital for successful implementation. To assess the success of the adaptation to a self-directed format, a mixed-methods design was employed, and Life Orientation teachers’ evaluative feedback was solicited (n = 11). Favorable quantitative results were obtained; majority of teachers agreed that learners enjoyed the booklet (manualized format) and that it was deemed an adequate substitute to the previous contact-based format of the Career Guidance Project. This was also confirmed by the qualitative findings revealing teachers’ satisfaction with the booklet’s content, specifically that the booklet is complementary to the Life Orientation curriculum. Qualitative findings identified specific contextual barriers that contributed to some learners struggling to use the booklet optimally. The results suggest that it is feasible and acceptable to implement a self-directed career guidance intervention among secondary school learners amid a global pandemic. Teachers recommended ways to integrate the booklet, resources and contact sessions as a preferred way forward. These findings have important implications for similar resource-constrained settings that may not have readily access to in-person career guidance and counselling human development. Keywords: career guidance1, secondary school learners2, teachers3, low-income communities4, resource-constrained schools5, mixed method6